Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "times", "divided by", "equals". Please use "brackets" (or parentheses) because it is impossible to work out whether sqrt 5x plus 1 is sqrt (5x + 1) or sqrt(5x) + 1.
If you mean: 2x^2 -5x = 35 then 2x^2 -5x -35 = 0 and by using the quadratic equation formula the value of x is (5-square root 305)/4 or (5+square root 305)/4
5x times the square root of y
The square root of anything to an even power is that thing to half the power. √(5x^13) = √(x^12 5x) = √(x^12) √(5x) = x^6 √(5x) But is that really any simpler?
There is a formula for the "difference of squares." In this case, the answer is (5x + 3)(5x - 3)
It is (x + y)^3 - sqrt(5x + 3y) and there is no sensible simplification of this expression.
a+ square root of b has a conjugate a- square root of b and this is used rationalize the denominator when it contains a square root. If we want to multiply 5 x square root of 10 by something to get rid of the radical you can multiply it by square root of 10. But if we look at 5x( square root of 10 as ) 0+ 5x square root of 10 then the conjugate would be -5x square root of 10
X2+5x-6. a=1, b=5, and c=-6 The formula is: -b plus or minus the square root of b squared minus 4ac all over 2a. -b+square root of b2-4ac ---- 2a -5 plus or minus the square root of 5 squared minus 4(1)(-6) -5 plus or minus the square root of 25-4(-6) -5 plus or minus the square root of 25+24 -5 plus or minus the square root of 49 -5 plus or minus 7 Here is where you split into two different answers: Number 1: -5 plus 7= 2 Number 2: -5 minus 7= -12 Your answer is X=2, -12
5x = sqrt(10) + 15x -10x = sqrt(10) x = -sqrt(10)/10 = -sqrt(10)
If you mean: 2x^2 -5x = 35 then 2x^2 -5x -35 = 0 and by using the quadratic equation formula the value of x is (5-square root 305)/4 or (5+square root 305)/4
5x times the square root of y
The square root of anything to an even power is that thing to half the power. √(5x^13) = √(x^12 5x) = √(x^12) √(5x) = x^6 √(5x) But is that really any simpler?
There is a formula for the "difference of squares." In this case, the answer is (5x + 3)(5x - 3)
5x
x = 0,1
It is (x + y)^3 - sqrt(5x + 3y) and there is no sensible simplification of this expression.
5x² - 18x + 9 = (5x² - 15x) - (3x - 9) = 5x(x - 3) - 3(x - 3) = (5x - 3)(x - 3).
Derivative with respect to 'x' of (5x)1/2 = (1/2) (5x)-1/2 (5) = 2.5/sqrt(5x)